Acyclic nucleoside phosphonates with adenine nucleobase inhibit Trypanosoma brucei adenine phosphoribosyltransferase in vitro - Eva Doleželová (Nature Portfolio, 2021)
Abstract All medically important unicellular protozoans cannot synthesize purines de novo and they entirely rely on the purine salvage pathway (PSP) for their nucleotide generation. Therefore, purine derivatives have been considered as a promising source of anti-parasitic compounds since they can act as inhibitors of the PSP enzymes or as toxic products upon their activation inside of the cell. Here, we characterized a Trypanosoma brucei enzyme involved in the salvage of adenine, the adenine phosphoribosyl transferase (APRT). We showed that its two isoforms (APRT1 and APRT2) localize partly in the cytosol and partly in the glycosomes of the bloodstream form (BSF) of the parasite. RNAi silencing of both APRT enzymes showed no major effect on the growth of BSF parasites unless grown in artificial medium with adenine as sole purine source. To add into the portfolio of inhibitors for various PSP enzymes, we designed three types of acyclic nucleotide analogs as potential APRT inhibitors. Out of fifteen inhibitors, four compounds inhibited the activity of the recombinant APRT1 with Ki in single µM values. The ANP phosphoramidate membrane-permeable prodrugs showed pronounced anti-trypanosomal activity in a cell-based assay, despite the fact that APRT enzymes are dispensable for T. brucei growth in vitro. While this suggests that the tested ANP prodrugs exert their toxicity by other means in T. brucei, the newly designed inhibitors can be further improved and explored to identify their actual target(s).